Design and fabrication of can presser / Muhammad Haqimie Mohd Nasri and Raja Muhammad Aslam Raja Arif - Mohd Nasri, Muhammad Haqimie; Raja Arif, Raja Muhammad Aslam (School of Mechanical Engineering, 2023)
A can presser is one of the tools that is being used to recycle plastic cans nowadays. However, these types of pressers can only crush one plastic can at a time. This will indeed affect the flow of work being put out by the workers that are using those can pressers. The main objective of this project is to increase the efficiency of the can presser. The internet has been used as one of the research platforms in conducting this final-year project. The outcome of this project is that it will help to reduce the operational time of the workers that are using this can presser.